2023
DOI: 10.1002/smll.202206100
|View full text |Cite
|
Sign up to set email alerts
|

1D and 2D Field Effect Transistors in Gas Sensing: A Comprehensive Review

Abstract: Rapid progress in the synthesis and fundamental understanding of 1D and 2D materials have solicited the incorporation of these nanomaterials into sensor architectures, especially field effect transistors (FETs), for the monitoring of gas and vapor in environmental, food quality, and healthcare applications. Yet, several challenges have remained unaddressed toward the fabrication of 1D and 2D FET gas sensors for real‐field applications, which are related to properties, synthesis, and integration of 1D and 2D ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 376 publications
(1,064 reference statements)
0
25
0
1
Order By: Relevance
“…20 The latter can be used to obtain structures with pronounced peculiarities in optical, electronic, and especially adsorption properties making them distinctive from bulk Si. 21 So, the development of highly sensitive and selective sensors based on Si NWs is a promising way for the mass production considered by many scientific groups. 22−25 In light of high demand in laboratories-on-a-chip, biosensors, and personalized medicine, the detection of substances found both in nature and produced in a human body is of particular interest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 The latter can be used to obtain structures with pronounced peculiarities in optical, electronic, and especially adsorption properties making them distinctive from bulk Si. 21 So, the development of highly sensitive and selective sensors based on Si NWs is a promising way for the mass production considered by many scientific groups. 22−25 In light of high demand in laboratories-on-a-chip, biosensors, and personalized medicine, the detection of substances found both in nature and produced in a human body is of particular interest.…”
Section: Introductionmentioning
confidence: 99%
“…Due to that, many growth and processing technologies have been developed for the fabrication of Si nanostructures including epitaxial techniques and etching methods . The latter can be used to obtain structures with pronounced peculiarities in optical, electronic, and especially adsorption properties making them distinctive from bulk Si . So, the development of highly sensitive and selective sensors based on Si NWs is a promising way for the mass production considered by many scientific groups. …”
Section: Introductionmentioning
confidence: 99%
“…Due to their extremely small quantum capacitance, the FETs built on individual s-SWCNTs have shown an ultra-high biomolecular charge sensitivity such that even slight variations in charge number or distribution can induce a substantial change in electrical conductance [ 49 ]. The capacity of individual CVD-derived CNT-based FETs has been demonstrated with respect to the detection of protein conformational motion dynamics at the single-molecule level [ 50 , 51 ].…”
Section: Carbon Nanotube Materialsmentioning
confidence: 99%
“…With the dispersed and purified s-CNT solution, a randomly distributed s-CNT thin film can be obtained via the dip-coating method at the wafer scale, and this solution-dispersed method can easily be scaled up [ 59 , 60 , 61 ]. The randomly oriented network film ensures homogenous properties and provides a solid foundation for reproducible device fabrication [ 49 , 62 , 63 , 64 , 65 , 66 ]. The wafer-scale uniform semiconducting CNT network films have proven to be an attractive option for FET biosensors due to their remarkable potential for meeting the requirements for industrialization.…”
Section: Carbon Nanotube Materialsmentioning
confidence: 99%
“…Pd was introduced at a certain concentration threshold to create nanofibers with a switch-like ultrahigh responsiveness and hydrogen selectivity . Paghi et al critically reviewed FET-based gas sensors using one- and two-dimensional nanostructures, highlighting the advantages and challenges of the sensor . Drozdowska et al demonstrated an efficient ZrS3-based photoactive FET sensor showing enhanced sensitivity for NO 2 , ethanol, and acetone on blue light exposure .…”
Section: Introductionmentioning
confidence: 99%